2018
DOI: 10.1016/j.oooo.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cell cycle proteins according to HPV status in oral squamous cell carcinoma affecting young patients: a pilot study

Abstract: No significant difference exists in the expression of cell cycle proteins studied between HR-HPV DNA-positive and HR-HPV DNA-negative OSCC affecting young patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 38 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…In addition, it was verified that amplification of c‐myc, assessed by real‐time PCR, was significantly associated with levels of its protein product. In another study, considering only nuclear staining, there was no statistical difference in the MYC expression between HR‐HPV DNA‐positive and ‐negative groups (Miranda Galvis et al., 2018). In the study by Popović et al.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In addition, it was verified that amplification of c‐myc, assessed by real‐time PCR, was significantly associated with levels of its protein product. In another study, considering only nuclear staining, there was no statistical difference in the MYC expression between HR‐HPV DNA‐positive and ‐negative groups (Miranda Galvis et al., 2018). In the study by Popović et al.…”
Section: Discussionmentioning
confidence: 95%
“…Other authors found no association between p53 expression and HPV presence as well, in which the viral detection was performed by PCR (Angiero et al., 2010; Emmett et al., 2017; Greer et al., 2008; Miranda Galvis et al., 2018; Nemes et al., 2006; Oliveira et al., 2009; Shindoh et al., 1995). Nonetheless, as in our study, Greer et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We conducted a retrospective study including 39 patients aged <45 years and a matched group of 38 patients aged ≥45 years with HNSCC treated at our University Hospital over a period of 13 years. There is currently no consensus in the literature regarding the threshold for differentiating between young and old patients, with previous authors using either 40 or 45 years; 6 , 20 22 We therefore chose 45 years as the age threshold to define young and old patients.…”
Section: Discussionmentioning
confidence: 99%